Work-family conflict and work-family facilitation relating employee burnout during COVID-19 in Thai hotel industry - Eason, Daniel (Prince of Songkla University, 2023)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2022